Ethno-medicinal Plant Resources of Tribal Pangi Valley in District Chamba, Himachal Pradesh, India - Dutt, Bhupender; Nath, Dina; Chauhan, N. S.; Sharma, K. R.; Sharma, S. S. (International Journal of Bio-resource and Stress Management, 2023)
Ethnobotanical studies provide helpful clues for crop domestication and folk selection for better utilization of resources to meet local needs.The rural folks and tribals in India even today depend largely on the local herbal resources for curing different types of diseases. The present study was undertaken to assess the ethno medicinal uses of plants by the tribal people of remote tribal Pangi valley of Himachal Pradesh, revealed 45 plant species belonging to 20 different families having ethno medicinal value. The information on ethno medicinal uses of plants was collected through interviews, questionnaires, direct observations and also by consulting local elderly people, Gujjars or Gaddies and Vaids. The local people believe in the efficacy of these herbs along with some divine power, but the knowledge is restricted to very few elderly folks only. Therefore, this valuable information needs to be systematically collected, documented and preserved so that it can serve the mankind in generation to come and will also act as an important tool in conserving and preserving the traditional usages of these precious plant resources of high economic value. The collected information has been documented and presented in the current study.